Poor Sleep Quality and Factors Among Reproductive-Age Women in Southwest Ethiopia - Bogale, Biruk; Wolde, Asrat; Mohammed, Nuredin; Midaksa, Gachana; Bekele, Bayu Begashaw (Frontiers in Psychiatry, 2022)
Background Adequate sleep is vital for physical and mental wellbeing. Sleep-related problems including poor quality of sleep have been increasing throughout the world among reproductive-aged women. Poor sleep quality has been related with number of diseases and health problems However, evidences are scarce regarding poor sleep quality and its associated factors among women of the reproductive age group in Ethiopia. Objective To assess sleep quality and associated factors among women of reproductive age group in Mizan Aman town, Southwest Ethiopia. Method Community-based cross-sectional study was conducted among 606 reproductive-aged women from 06 November to 20 December 2020, in Mizan Aman town. Data were collected using structured interview administered questionnaires. Pittsburgh Sleep Quality Index (PSQI) was used to assess sleep quality. Multivariable logistic regression was applied using an adjusted odds ratio with a corresponding 95% confidence interval to evaluate the statistical significance of associated factors. Result The overall prevalence of poor sleep quality was 71.3%. The late age group of 42–49 (AOR, 95% CI; 1.21 (1.08–5.76), palpable/visible thyroid gland (AOR, 95% CI; 2. 12 (1.08–3.82), current substance use (AOR, 95% CI; 1.76 (1.11–6.10) and having premenstrual syndrome (AOR, 95% CI; 1.86 (1.38–3.12) were significantly associated with poor sleep quality among reproductive age group women. Conclusion Significant majority of reproductive age group women faced poor sleep quality. Therefore, screening of sleep patterns among this particular age group is warranted. Moreover, education about sleep hygiene needs to be given considering the identified factors to improve sleep quality.